First Principles Calculation of the Structure and Dielectric Properties of Bi2Ti2O7 - PATTERSON, CHARLES (My University, 2010)
The structure, vibrational modes, and phonon contribution to the dielectric function of the pyrochlore Bi 2 Ti 2 O 6 O were calculated using first-principles methods. Total-energy minimization calculations were per- formed for Bi 2 Ti 2 O 6 O in a unit cell containing 88 ions, which had the ideal, cubic pyrochlore structure as the initial configuration. No symmetry constraints were imposed during this relaxation. Subsequent symmetry analysis of the relaxed structure found Pna 2 1 space-group symmetry in a 44 ion unit cell. This structure contains Bi ions with two types of eightfold coordination by O and O ions. Vibrational modes and the dielectric function were calculated for the Fd 3 ̄ m , Pna 2 1 , and P 1 structures. The crystal structure obtained by total-energy minimization is compared to structural data from reverse Monte Carlo analysis of neutron total scattering data. The imaginary part of the dielectric function derived from vibrational mode calculations is compared to dielectric function data for several related pyrochlores. Phonons which make the largest contri- butions to the dielectric constant are identified and analyzed.
PUBLISHED
Keywords: Physics; Nanoscience & Materials